STRATEGI PENGGERAK PEMBINA GENERUS (PPG) LDII DESA GUNUNG AGUNG DALAM PENGEMBANGAN KARAKTER RELIGIUS GENERASI MUDA - Elma Tiara Familiana; Suhandi Suhandi; Willia Novi Aryani (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The purpose of this study is to determine the strategies and work programs of the LDII Penggerak Pembina Generus (PPG) in Gunung Agung Village in fostering the religious character of the younger generation. This study uses descriptive qualitative research. The data sources used in this study were primary and secondary data. The data collection techniques used were interviews, observation, and documentation. The theory used was Talcott Parsons' structural functional theory. The findings and results of this study show that the younger generation in Gunung Agung Village has so far demonstrated religious character in line with the guidance targets, such as making it a habit to pray before carrying out activities, instilling an attitude of ta'dhim both in religious study groups and outside of them, refraining from physical contact with the opposite sex, making it a habit to read the Qur'an regularly and respecting elders by cultivating smiles, greetings, and salutations. Penggerak Pembina Generus (PPG) LDII of Gunung Agung Village has a strategy in fostering the religious character of the younger generation by creating work programs, making schedules for the socialization of these work programs, involving the 5 Elements of Generus Development, holding regular recitation activities, striving to achieve targets, and finally conducting development evaluations. The work program in religious character building for the younger generation is the 29 Noble Characters program, which includes this program includes the Tri Success of Generous, 6 NobleThobiat, 4 Ropes of Faith, 3 Work Principles, 4 Maqodirullah, 4 Rotating Wheels, and 5 Terms of Harmony and Compactness and dividing religious study classes based on age levels.